Heath risk assessment of heavy metals in shrimp Acetes sp. and cincalok collected in 2007 from Pantai Klebang, Peninsular Malaysia - Yap, Chee Kong; Cheng, Wan Hee; Ali, Mohd Hafetz; Nulit, Rosimah; Peng, Shih Hao Tony; Ismail, Mohamad Saupi; Leow, Chee Seng; Yap, Chee Wah (Journal of Toxicology and Risk Assessment, 2019)
Samples of shrimp (Acetes sp.), were collected from Pantai Klebang (Malacca, Peninsular Malaysia) in 2007. The mean metal concentrations (µg/g dry weight) in the total tissue of the shrimps were 1.47 for Cd, 7.10 for Cu, 41.5 for Fe, 3.70 for Ni, 4.49 for Pb and 27.1 for Zn. The metal levels (µg/g dry weight) in the shrimps are lower than Cd (1.47), Cu (8.55), Ni (4.19), and Pb (4.86). However, the levels of Fe (21.2) and Zn (11.0) in the cincalok were lower than those in the collected shrimps. For the human health risk assessment, all values of target hazard quotient for the six metals in the adults of Malaysian population were found below 1.00. This showed that there was no non-carcinogenic risk of the six metals via the consumption of Acetes sp. from the present study. However, regular monitoring of heavy metals in this popular small shrimps is still needed.